A web-based online tutorial in automata and languages theory - Saren, Vanessa A. (2005)
This project developed a software called Online tutorial system in Automata and Language /theory (OTSALT). This is a web-based application, which makes the tutorial on Automata and Languages Theory available on the Internet. The lessons in the tutorial are compilations of article files found in the Internet and Computer Science books. The topics included in the tutorial are verified and validated by the subject instructor of Automata Languages theory. Other Computer Science major subjects are not available in this online tutorial. This system is an automated manual of the subject. It provides security and ensures privacy by using a logon procedure for the users. There are two types of users in the system, the administrator and the students or the common users. The administrator has access to the database where the series of questions for the evaluation of users and the users profile accounts are stored. The administrator has the authority to manipulate any data stored in the database to maintain reliability of the tutorial. The other type of user, the student or learner, must be register to access the system. Each user has a unique username and password. There is a review exercise at the end of each chapter to evaluate the performance of each student and to determine whether he or she can proceed to the next chapter. This review exercise is a special feature of the system. The system reduces the time spent in searching about the subject because all information related to it are published in just one website. This would even serve as an additional reference to the students for self-study. It also ensures user- friendliness by providing a user?s manual for first-time users. The system was not designed dynamically. So, the system cannot add or post new topics on the subject that a learner needs. The user is recommended to use an Internet Explorer for better viewing of the tutorial
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2005